THE EFFECTIVENESS OF ENGLISH SINGSING YOUTUBE CHANNEL ON THE VOCABULARY MASTERY OF THE 2nd GRADE STUDENTS OF SDN KEPATIHAN BANYUWANGI - -, Tri Mulyati; Aning Safrani; Sutami Dwi Lestari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
The use of Youtube app among young learners has become a phenomenon. Obviously, watching YouTube videos is not always a bad thing. If the teachers and the parents lead them on selective topic watched like on vocabulary topics, it will have a positive impact on kids’ vocabulary mastery. This research aims to investigate whether there is any effect of English Singsing YouTube channel on the vocabulary mastery of the 2nd grade students of SDN Kepatihan. The pre experimental research design was employed with 29 respondent of 2nd grade were involved. Multiple choice test is chosen for the data collecting method that consist 20 questions of concrete nouns for the test. For the data analysis is used t-test formula. The researcher found that there is enhancement on the post-test. The mean score was 61,72 in the pre-test and 87,06 in the post-test. The result of t-test is higher than t-table (12,87 > 1,70). The researcher concluded that there is significant effect of English Singsing YouTube Channel on the Vocabulary mastery of the 2nd grade students of SDN Kepatihan Banyuwangi.